1986
DOI: 10.1021/bi00359a012
|View full text |Cite
|
Sign up to set email alerts
|

Human von Willebrand factor: a multivalent protein composed of identical subunits

Abstract: A large-scale method for the isolation of von Willebrand factor (vWF) from human factor VIII concentrates was developed in order to study the structure of this protein and its platelet binding activity. vWF is composed of a number of glycoprotein subunits that are linked together by disulfide bonds to form a series of multimers. These multimers appear to contain an even number of subunits of 270K. Two minor components of Mr 140K and 120K were also identified, but these chains appear to result from minor proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
67
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 56 publications
10
67
0
1
Order By: Relevance
“…25,26 In the present study, neither UL nor increased LMW multimers of vWF were consistently found in TMA. This discrepancy concerning the LMW multimers may be methodologic because we chose the first 5-mers to define the LMW forms, 29 whereas Galbusera and colleagues chose the 2 fastest migrating bands of the multimeric profile. 25,26 Furthermore, searching for statistical relationships between vWFcleaving protease and other laboratory features may be interesting to establish a pathogenic link between vWF-cleaving protease deficiency and the variation of the multimeric profile of vWF.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In the present study, neither UL nor increased LMW multimers of vWF were consistently found in TMA. This discrepancy concerning the LMW multimers may be methodologic because we chose the first 5-mers to define the LMW forms, 29 whereas Galbusera and colleagues chose the 2 fastest migrating bands of the multimeric profile. 25,26 Furthermore, searching for statistical relationships between vWFcleaving protease and other laboratory features may be interesting to establish a pathogenic link between vWF-cleaving protease deficiency and the variation of the multimeric profile of vWF.…”
Section: Discussionmentioning
confidence: 99%
“…vWf has a central role in platelet adhesion and additionally is a carrier protein for coagulation factor VIII (1). It is a large multimeric protein built from identical subunits (2). The assembly of subunits gives rise to a series of multimers with molecular masses varying between 500 and 20,000 kD.…”
Section: Introductionmentioning
confidence: 99%
“…were BJV-VIIIcp, 28 kDa (by NaDodSO4/PAGE); fVIII, 200 kDa (average of the heterodimeric mixture by NaDodSO4/ PAGE); fVIIIaIia and fVIIIaBJ, 160 kDa (7); thrombin, 37 kDa (14); vWf subunit, 270 kDa (19).…”
mentioning
confidence: 99%